2002
DOI: 10.5014/ajot.56.4.422
|View full text |Cite
|
Sign up to set email alerts
|

Stigma and Its Management: A Pilot Study of Parental Perceptions of the Experiences of Children With Developmental Coordination Disorder

Abstract: The findings of a small qualitative interview study with 8 parents of 6 children with developmental coordination disorder are reported. The parents discussed the social consequences of their children's motor difficulties. The new International Classification of Functioning, Disability and Health was used as a framework for the analysis of the interview transcripts. The analysis revealed that the parents believed that their children's impairments restrict their participation in society. The interactions between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
0
17

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(86 citation statements)
references
References 7 publications
1
68
0
17
Order By: Relevance
“…However, negative attitudes such as stigmatizing, stereotyping and discrimination may impact on motivation to participate in social activities with others. Studies reporting on the relationships between parents and children with DCD suggest that family members often experience frustration and anxiety over the child's inability to manage simple tasks [49,103]. As a result, children with DCD are likely to believe that they are disappointing their parents, which may worsen their feelings of low self-worth [6].…”
Section: Attitudesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, negative attitudes such as stigmatizing, stereotyping and discrimination may impact on motivation to participate in social activities with others. Studies reporting on the relationships between parents and children with DCD suggest that family members often experience frustration and anxiety over the child's inability to manage simple tasks [49,103]. As a result, children with DCD are likely to believe that they are disappointing their parents, which may worsen their feelings of low self-worth [6].…”
Section: Attitudesmentioning
confidence: 99%
“…The relationship between parents and children with DCD can be described as anxious; as parents worry that their children's impairments would restrict participation in society [103].…”
Section: Support and Relationshipsmentioning
confidence: 99%
“…These authors concluded that the level of detail needed for a richer description of the functioning of a patient does not yet exist within the ICIDH or the ICF classification systems. Segal, Mandich, Polatajko, and Valiant-Cook (2002) described an application of the ICF in occupational therapy in the United States, a pilot study of stigma and its management, in which ICF codes were used to examine parental perceptions of the experiences of children with developmental coordination disorders. The analysis revealed that the parents believe that their children's impairments restrict their participation in society.…”
Section: Nursingmentioning
confidence: 99%
“…Os resultados deste estudo apontam associação de provável TDC com sinais de TDAH (Tabela 2), especialmente dos tipos desatento e combinadodesatenção com hiperatividade, o que também é apontado na literatura internacional 3,[6][7][8][9] . Em estudo realizado no Brasil, Cardoso et al 16 observaram que, considerando a frequência de TDAH, com base em respostas de professores ao SNAP-IV, dentro do grupo TDC, 41,2% mostraram sinais de TDAH: seis crianças com TDC (17,6%) exibiam sinais de déficit de atenção, uma (2,9%) apresentou sinais de hiperatividade/impulsividade, sete (20,7%) apresentaram sinais de TDAH combinado, 18 (52,9%) não apresentaram sinais de TDAH e dois (5,9%) não retornaram os questionários.…”
Section: Discussionunclassified
“…Geralmente a criança tem inteligência normal, mas os problemas de coordenação motora grossa e fina podem interferir no rendimento escolar e em atividades de vida diária (AVD)¹ , ². Os traços mais comuns de se observar nessas crianças são problemas na habilidade motora fina, função motora grossa, coordenação geral e controle durante a execução do movimento, dificuldade para executar atividades típicas da infância como jogar bola, escrever, andar de bicicleta, vestir roupas, amarrar cadarços e utilizar tesoura, talheres e outros utensílios domésticos, atrapalhando desta forma a execução das AVD, atividades de brincar e tarefas escolares 2,3,4,5 . Além dos problemas de coordenação motora que refletem no cotidiano da criança, podem ser percebidas co-ocorrências associadas como a obesidade, problemas de saúde mental e o transtorno do déficit de atenção e hiperatividade (TDAH), podendo trazer mais prejuízos funcionais 3,6,7,8,9 . Estudos epidemiológicos indicam que a prevalência de TDC pode variar de 5 a 9% em crianças em idade escolar, sendo que a maior parte delas é do sexo masculino, não importando o nível socioeconômico¹ 0 .…”
Section: Introductionunclassified